A city of men? An ethnographic enquiry into cultures of youth masculinities in urban India - Philip, S (2018)
The gender order in urban India is changing rapidly. Several economic, political and sociocultural shifts have brought with them new opportunities and challenges for Indian men and women. This thesis attempts to understand some of these social and cultural changes from the perspective of a group of affluent young men in Delhi. By ethnographically studying young men and their masculinities in urban public spaces of leisure and consumption, this thesis explores some of their relatively new practices of consumption and embodied performances of gender, as well as its consequences on gendering a city space. Through focusing on newly commodified spaces like gyms, shopping malls, night clubs, bars, metro trains and cruising parks in Delhi, I argue that a politics of space, age, gender and class come together to mark men’s identities, bodies as well as urban spaces, creating forms of belonging and exclusions in a neoliberal India. Within this context, I explore how ideas of what it means to be a young man are changing in a consumerist India and how this in turn shapes young men’s relationships with other men, women, families and changing city spaces. Using ethnographic data collected over fourteen months of fieldwork in Delhi, along with visual and cultural analysis, this thesis lays bare the layers of masculine performances and reveals the everyday attempts at embedding and reproducing a heterosexist patriarchal social order under the guise of a ‘new Indian man’ and his ‘new’ India. In the process, I critically but empathetically explore the gendered hierarchies and anxieties that emerge in contemporary India and its consequences on various bodies and city spaces. The chief arguments are presented in five empirical chapters: 1) A ‘New’ Indian Man, 2) A Masculine Body, 3) Desexing a Masculine Body, 4) A Smart and Masculine City, and 5) A Safe/Unsafe City.